Plasmalogens Eliminate Aging-Associated Synaptic Defects and Microglia-Mediated Neuroinflammation in Mice - Gu, Jinxin; Chen, Lixue; Sun, Ran; Wang, Jie-Li; Wang, Juntao; Lin, Yingjun; Lei, Shuwen; Zhang, Yang; Lv, Dan; Jiang, Faqin; Deng, Yuru; Collman, James P.; et al. (Frontiers in Molecular Biosciences, 2022)
Neurodegeneration is a pathological condition in which nervous system or neuron losses its structure, function, or both leading to progressive neural degeneration. Growing evidence strongly suggests that reduction of plasmalogens (Pls), one of the key brain lipids, might be associated with multiple neurodegenerative diseases, including Alzheimer’s disease (AD). Plasmalogens are abundant members of ether-phospholipids. Approximately 1 in 5 phospholipids are plasmalogens in human tissue where they are particularly enriched in brain, heart and immune cells. In this study, we employed a scheme of 2-month Pls intragastric administration to aged female C57BL/6J mice, starting at the age of 16 months old. Noticeably, the aged Pls-fed mice exhibited a better cognitive performance, thicker and glossier body hair in appearance than that of aged control mice. The transmission electron microscopic (TEM) data showed that 2-month Pls supplementations surprisingly alleviate age-associated hippocampal synaptic loss and also promote synaptogenesis and synaptic vesicles formation in aged murine brain. Further RNA-sequencing, immunoblotting and immunofluorescence analyses confirmed that plasmalogens remarkably enhanced both the synaptic plasticity and neurogenesis in aged murine hippocampus. In addition, we have demonstrated that Pls treatment inhibited the age-related microglia activation and attenuated the neuroinflammation in the murine brain. These findings suggest for the first time that Pls administration might be a potential intervention strategy for halting neurodegeneration and promoting neuroregeneration.